Cultural Acculturation and Symbolic Meaning in the Architecture of the Bagas Godang of the Huristak Kingdom, Padang Lawas - Nofi Dayanti Siregar; Nabila Yasmin (Warisan: Journal of History and Cultural Heritage, 2026)
This study examines the architecture of the Bagas Godang of the Huristak Kingdom in Padang Lawas, a cultural heritage with historical, social, and symbolic significance. Previous studies on Mandailing traditional architecture have primarily emphasized physical forms and typologies, while paying limited attention to the transformation of social functions and cultural acculturation embodied in the Huristak Bagas Godang. This study aims to analyze the evolution of its social functions, architectural characteristics, and cultural meanings. Employing a historical approach within a descriptive-analytical framework, the research applied heuristics, source criticism, interpretation, and historiography. Data were collected through field observations, interviews with traditional leaders, and a literature review. The findings indicate that Bagas Godang Huristak has transformed from a center of traditional authority into a cultural institution that remains relevant in contemporary society. Architecturally, the building reflects an acculturation of Mandailing and Malay traditions, evident in its structural system, roof form, spatial organization, and ornamental motifs. This study contributes to traditional architecture and heritage studies by demonstrating that Bagas Godang serves not only as an architectural artifact but also as a symbol of cultural identity, social continuity, and historical adaptation, underscoring its importance for preservation.